GLI2 inhibits cisplatin sensitivity in gastric cancer through DEC1/ZEB1 mediated EMT - Wenshuai Zhu; Jingguo Sun; Fubo Jing; Yuanxin Xing; Muhua Luan; Zhaotian Feng; Xiaoli Ma; Yunshan Wang; Yanfei Jia (Cell Death and Disease)
Abstract Cisplatin (CDDP) based chemotherapy has emerged as the predominant therapeutic regimen for patients with advanced gastric cancer (GC). However, its efficacy is dampened by the development of chemoresistance, which results in poor prognosis of patients. GLI2, a key transcription factor in the Hedgehog (Hh) signaling pathway, is regarded as a target for cancer therapy. However, the significance of GLI2 for CDDP resistance in GC has not been well established. Here, we show that GLI2 expression was upregulated in EMT-type GC and associated with poor prognosis. GLI2 promotes proliferation, migration, and CDDP resistance of GC cells by inducing EMT. In terms of mechanism, GLI2 binds to the promoter region of DEC1 and enhances its expression, thereby co-transcriptionally regulating ZEB1 expression. Animal experiments have demonstrated that both GLI2 knockdown and GLI2 inhibitor significantly enhance CDDP sensitivity in GC. Our data not only identify a novel GLI2/DEC1/ZEB1/EMT pathway in GC CDDP resistance but also provide novel strategies to treat GC in the future.